2022
DOI: 10.1530/rep-22-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol and IGF1 on glycogen synthesis in bovine uterine epithelial cells

Abstract: Glycogen storage in the uterine epithelium peaks near estrus and is a potential source of glucose for the endometrium and embryos. However, the hormonal regulation of glycogen synthesis in the uterine epithelium is poorly understood. Our objective was to evaluate the effect of estradiol (E2) and insulin-like growth factor 1 (IGF1) on glycogenesis in immortalized bovine uterine epithelial (BUTE) cells. Treatment of BUTE cells with E2 (0.1-10 nM) did not increase glycogen levels. However, treatment of BUTE cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…In addition, estradiol treatment increased glucose utilization and metabolism via glycolysis in uterine homogenates in immature rats ( Baquer & McLean 1972 ). Another study found that estradiol stimulated IGF1 in the uterine stroma of cows, which agrees with studies from mice ( Cooke et al 1997 , Gonzalez et al 2022 ). IGF1 increased the levels of 3-phosphoglycerate and lactic acid in immortalized bovine uterine epithelial (BUTE) cells ( Gonzalez et al 2022 ).…”
Section: Metabolism and Secretion Of Nutrients By The Uterine Epitheliumsupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, estradiol treatment increased glucose utilization and metabolism via glycolysis in uterine homogenates in immature rats ( Baquer & McLean 1972 ). Another study found that estradiol stimulated IGF1 in the uterine stroma of cows, which agrees with studies from mice ( Cooke et al 1997 , Gonzalez et al 2022 ). IGF1 increased the levels of 3-phosphoglycerate and lactic acid in immortalized bovine uterine epithelial (BUTE) cells ( Gonzalez et al 2022 ).…”
Section: Metabolism and Secretion Of Nutrients By The Uterine Epitheliumsupporting
confidence: 77%
“…Another study found that estradiol stimulated IGF1 in the uterine stroma of cows, which agrees with studies from mice ( Cooke et al 1997 , Gonzalez et al 2022 ). IGF1 increased the levels of 3-phosphoglycerate and lactic acid in immortalized bovine uterine epithelial (BUTE) cells ( Gonzalez et al 2022 ). Collectively, these results suggest that estradiol increases glucose uptake and glycolytic metabolism by the uterine epithelium, perhaps indirectly.…”
Section: Metabolism and Secretion Of Nutrients By The Uterine Epitheliumsupporting
confidence: 77%
See 2 more Smart Citations
“…Western blots were performed as previously described (Gonzalez et al, 2022;Sandoval et al, 2021). Protein was separated on a 10% SDS-PAGE gel and was transferred onto a PVDF membrane, and membranes were blocked with 5% BSA in TBS-T. Anti-GAA (1:1000; ab137068, Abcam) or α-tubulin (1:500; 2144, Cell Signaling) antibodies were diluted in 5% BSA, added to the membranes and incubated overnight at 4°C.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%